Shoe midsole longitudinal bending stiffness and running economy, joint energy, and EMG - Roy, J. P. R.; Stefanyshyn, D. J. (Medicine & Science in Sports & Exercise, 2006)
Purpose: It has been shown that mechanical energy is dissipated at the metatarsophalangeal (MTP) joint during running and jumping. Furthermore, increasing the longitudinal bending stiffness of the midsole significantly reduced the energy dissipated at the MTP joint and increased jump performance. It was hypothesized that increasing midsole longitudinal bending stiffness would also lead to improvements in running economy. This study investigated the influence of midsole longitudinal bending stiffness on running economy (performance variable) and evaluated the local effects on joint energetics and muscular activity.